Dedolomitization and reservoir quality: insights from reactive transport modelling. Issue 2 (28th February 2013) - Escorcia, L‐.C.; Gomez‐Rivas, E.; Daniele, L.; Corbella, M.
Abstract Dedolomitization or calcitization, the replacement of dolomite by calcite, modifies the porosity and permeability of carbonate rocks. This study evaluates the effects of dedolomitization on the porosity of carbonates by means of geochemical and reactive transport simulations. The obtained results indicate that dedolomitization is a slow process that may be triggered by cold meteoric water but also by warm groundwater at temperatures of ≤50°C. Dedolomitization is more efficient with fluid fluxes on the order of tens of metres per year. Most of the simulations performed in this study resulted in a loss of porosity due to calcitization. The rate of the dedolomitization reaction increases significantly when calcium‐bearing minerals with faster dissolution kinetics and smaller molar volume than calcite, such as anhydrite, are present in the system. In such situations, the porosity of the rock increases significantly (approximately 10%) during a time span of hundreds of thousands of years. Therefore, depending on its original composition, fluid flow conditions and fluid composition, the porosity of a tight dolostone can be enhanced and reach porosity values of reservoir rocks after being calcitized.